APPLICATION OF QUIPPER SCHOOL-BASED BLENDED LEARNING TO IMPROVE STUDENTS' MOTIVATION AND LEARNING OUTCOMES IN ACID-BASED MATERIALS AT SMAN 5 BANDA ACEH - Putri Melia; Sulastri Sulastri; Rusman Rusman (Chimica Didactica Acta, 2022)
This research aims to investigate the increase in learning motivation, learning outcomes, learning activities, and student responses to blended learning on acid-base material through Quipper School. The research subjects of class XI MIA 1 students of SMAN 5 Banda Aceh for the 2021/2022 academic year are even semesters involving 32 students. The data collection technique uses a simple random sampling technique. The instruments used in this study were learning outcomes test questions, motivational questionnaire sheets, activity observation sheets, and student response questionnaire sheets.  Analysis of learning motivation data using motivational questionnaires adapted from MSLQ using a likert scale, learning outcomes data using LKPD and tests (pretest-postest), activity data using activity sheets and response data collected through questionnaire sheets. The results showed that there was a change in the previous 63.67%, learning motivation after the blended learning process, the students’ learning motivation became 68,15%, this happened in Quipper School-based blended learning. The average completeness of student learning is 80, including the very high category. The positive response of student to blended learning was 72.2%. The activities of students during blended learning get an average score of 95%. Based on the results of the study, it can be concluded that the application of blended learning can change learning motivation and exceed the KKM of student learning outcomes at SMAN 5 Banda Aceh.